Ordbok eller encyklopedi - en fråga om hänsyn till användaren? - Ruppel, Klaas (Nordiske Studier i Leksikografi, 1997)
The object of my study is in which way the meanings of the headwords are explained in the entries ofthe Finnish etymological dictionary that is being compiled at the Research Institute for the Languages ofFinland (Suomen sanojen alkuperä, "The Origin of Finnish Words", 1-2. A-P. Helsinki 1992-95). The dictionary is Finnish, and thus the metalanguage is the same as the target language. In addition to definitions or explanations in Finnish also another metalanguage, German, is used. In some cases the meaning is defined only in German. My article illustrates the factors that play a part in the usage of the second metalanguage, problems brought by the use of double definitions, and what background data are necessary for the users in order to understand the explanations.